The Effect of Talent Management and Workload on Employee Performance with Competence as a Mediating Variable at BPS-Statistics Indonesia across Maluku Province - Richie Maulana Yusuf; Conchita V. Latupapua; Agusthina Risambessy (LP2M IAIN Palopo, 2026)
This research was conducted to obtain an explanation regarding the effect of talent management and workload on employee performance with competence as a mediating variable at BPS-Statistics Indonesia across Maluku Province. The purpose of this research is to analyze the effect of talent management and workload on employee performance with competence as a mediating variable. This research uses quantitative research. This research uses smartPLS version 4 software, the data collection instrument is a questionnaire measured using a Likert scale. This study had a sample of 191 respondents, namely employees of the BPS-Statistics Indonesia across Maluku Province. The results of this research show that Talent Management has a significant effect on employee performance with a p value of 0.018 < 0.05, the Workload has a significant effect on Employee Performance with a p value of 0.000 < 0.05, Talent Management has a significant effect on Competency with a p value of 0.000 < 0.05, Workload has a significant effect on Competency with a p value of 0.000 < 0.05, Competency has a significant effect on Employee Performance with a p value of 0.000 < 0.05, Competency mediate between Talent Management and Employee Performance with a p value 0.000 > 0.05, Competency mediate between the Workload and Employee Performance at BPS-Statistics Indonesia across Maluku Province.